Assessing “the Religious” and “the Secular” in the Pilgrimage to Gus Dur’s Grave - Sya'rani, Afifur Rochman (Jurnal Sosiologi Agama, 2018)
Abdurrahman Wahid, well-known as Gus Dur, is the fourth president of Indonesia. He was also the leader of Nahdlatul Ulama’ (NU), the largest Muslim organization in the country. Located in the area of Pesantren (Islamic boarding school) Tebuireng, Jombang, East Java, his grave is one the most visited places for pilgrimage, not only in Java, but also in Indonesia. It is reported that in 2017, “more than 3.000 people visit the grave per day, and can increase three times as much during Saturday and Sunday”. Due to the growing number of visitors, the grave has been renovated, and infrastructural facilities have been built, including the establishment of museum, monument, library, and area of parking. It is noteworthy that pilgrimage to particular religious sites has been called as wisata religi (religious tourism). For example, Gus Dur’s grave has been awarded as the best religious tourism in East Java by Anugerah Wisata Jawa Timur (AWJ) in 2017. This is interesting, as it implies that pilgrimage is not always religious, but also may contain secular instances. This article, thus, seeks to investigate how the religious and the secular go hand in hand in the context of pilgrimage by using Gus Dur’s grave as a case of study. I would argue that the problems should be putted in the context of debate over pilgrimage and tourism, considering that the term wisata religi or religious tourism has been attributed to religious sites and gravesites in particular which have been objectified as a tourist site. Pilgrimage is not merely about religious-based practices, but also about tourist practices. Therefore, this implies that pilgrimage and tourism cannot be viewed in a binary opposition. In the context of global tourism, both are intertwined and overlapped in some ways. In other words, pilgrimage may contain both religious and secular elements. Keywords: Gus Dur’s Grave, Pilgrimage, Tourism, Religious, Secular